The First Bagshawe lecture. Towards generating cytotoxic agents at cancer sites. - Bagshawe, K. D. (Nature Publishing Group, 1989)
Several years of experience have now accumulated in the targeting of anti-cancer agents so that we can take stock, identify problems and look for ways round them. Three major obstacles seem to limit present approaches. These are heterogeneity in the distribution of target molecules within the cancer cell population, the pharmacokinetic characteristics of macromolecules and host antibody response to foreign protein. An approach which we have been investigating uses antibodies or other vectors to carry enzymes which have no close human homologue to tumour sites. After clearing residual enzyme activity from the blood by one of several possible techniques, a relatively non-toxic prodrug is given. This prodrug is a substrate for the tumour located enzyme which results in the generation of a highly toxic molecule able to penetrate the tumour mass and cross cell membranes. Genetic engineering methods now offer the prospect of human immunoglobulins with tumour binding and catalytic sites having the potential to minimise host response. Whether this can be achieved depends on having antibodies with adequate specificity and our ability to develop enzyme-prodrug systems with the required characteristics. Early results encourage us to think progress can be made in this direction.